A new graph-based flight planning algorithm for unmanned aircraft system traffic management - Bae, Sangjun; Shin, Hyo-Sang; Tsourdos, Antonios (Institute of Electrical and Electronics Engineers (IEEE), 2018)
To efficiently and safely provide various types of services, small Unmanned Aircraft System (sUAS) are envisioned to be integrated with other airspace users. sUAS operation types such as route network, free flight, free routing can be determined depending on services, operating environments, etc. This paper addresses a route network-based flight planning problem that includes separation considered routing and scheduling for multiple sUASs. We propose an algorithm that generates each a route and schedule for each flight from its origin to its destination to minimise each sUAS' flight time while satisfying the minimum separation requirement at all times. The algorithm consists of an inner loop and an outer loop. In the inner loop each sUAS optimises its flight plan by solving its unique shortest path problem in a decentralised way. In the outer loop one of the flights is allocated using a centralised algorithm in each outer loop. The algorithm continues until all flights are allocated. As a preliminary study, we demonstrate the proposed algorithm through case studies for “last-mile delivery”, and “first-mile delivery”. The main contributions of this paper are as follows: increasing a solution search space by solving routing and scheduling problems simultaneously with separation assurance; low computational time. The proposed algorithm can be potentially applied to airspace capacity estimation and throughput of service points.